The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15405/epsbs.2018.05.27
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Readiness Towards Integrating Stem Education Into Teaching And Learning

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…As a result, this research proposes that readiness should be included in the influencing factors of STEM educational intention; thus, readiness was divided into three dimensions: cognition, emotion, and behavior [35][36][37] Certain extensions of the DTPB model were established: nine independent variables, four intervening variables, and one dependent variable were used to construct a comprehensive model. Furthermore, corresponding hypotheses were formulated, as shown in Figure 1.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…As a result, this research proposes that readiness should be included in the influencing factors of STEM educational intention; thus, readiness was divided into three dimensions: cognition, emotion, and behavior [35][36][37] Certain extensions of the DTPB model were established: nine independent variables, four intervening variables, and one dependent variable were used to construct a comprehensive model. Furthermore, corresponding hypotheses were formulated, as shown in Figure 1.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Teachers' teaching practices still employ a teacher-centered approach, which obstructs the development of higher-order thinking skills (HOTS) (MOE, 2013). Previous studies reported that integrated STEM teaching practices among teachers are still at a moderate level (Mahmud et al, 2018), incomprehensive (Mustafa et al, 2017), and unable to meet students' needs (Siew et al, 2015). The decline in students' academic performance is also linked to teachers' guidance methods, which do not suit the students' abilities (Losius et al, 2018;Nasir et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%
“…Of that number, 26.6 percent chose Technical and Vocational Education and Training (TVET). This decline could be linked to teachers' integrated STEM teaching practices which were reported to still be at a moderate level [12], not comprehensive [13], and not enough to meet the needs of the students [14]. The students were also reported to lack understanding of the teachers' delivery method and thus, causing them to lose interest in STEM [15][16][17].…”
Section: Introductionmentioning
confidence: 99%